A new variant of arcelin in wild common bean Phaseolus vulgaris L., from southern Mexico - Acosta Gallegos, Jorge Alberto; Quintero, C.; Vargas Daza, Jaime; Toro Chica, Orlando; Tohme, Joseph M.; Cardona Mejía, César (Springer, 1998)
Arcelin, a seed protein discovered in wild Phaseolus vulgaris L. accessions, gives high levels of resistance to the Mexican bean weevil [MBW; Zabrotes subfasciatus (Boheman)]. Six variants of arcelin have been described. In this paper we report on a new variant, arcelin 7, found in six wild bean accessions collected in the southern state of Chiapas in Mexico. The new variant is clearly distinct from previously reported ones. It confers high levels of resistance to MBW, comparable to those due to the presence of arcelin 1, arcelin 2 and arcelin 4. Accessions containing arcelin 7 were not as resistant as the one containing arcelin 5 but significantly better in terms of resistance than arcelins 3 and 6. Arcelin 7 was found in a poorly sampled area of Mexico threatened with genetic erosion due to expanding agricultural operations. This exemplifies the need for urgent additional collecting efforts.